Pemberdayaan Masyarakat untuk Pengelolaan Sampah Berkelanjutan di Kawasan Ekowisata Sungai Pisang: Sustainable Community-Based Waste Management for Supporting Ecotourism Development in Sungai Pisang, Bungus Teluk Kabung District, Padang - Randy Novirsa; Frima Elda; Yessy Markolinda; Fadilla Azmi (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2026)
Sungai Pisang, located in Teluk Kabung Selatan Subdistrict, Padang City, Indonesia, is a coastal area with considerable ecotourism potential but faces persistent challenges in household solid waste management. The community generates approximately 2.6 tons of plastic waste each month; however, the absence of temporary waste storage facilities and regular collection services has led to open burning and indiscriminate waste disposal, threatening public health and coastal ecosystems. This community engagement program aimed to strengthen local capacity for sustainable waste management through participatory and educational approaches. The program was implemented from January to December 2025 using a community-based participatory approach involving 30 participants representing women’s groups, youth organizations, the local Waste Management Institution, elementary school teachers, and community leaders. Activities included stakeholder coordination meetings, focus group discussions (FGDs), and community education on household waste segregation. The program improved participants' knowledge and practical skills in waste segregation. FGDs identified two feasible community-based waste management strategies: household composting of organic waste and periodic collection of recyclable inorganic waste. In addition, the Environmental Agency recommended establishing a Reduce, Reuse, and Recycle (3R) Waste Processing Facility (TPS3R) as a long-term solution to overcome geographical constraints affecting waste transportation to the Air Dingin landfill. Overall, the program enhanced community awareness, strengthened stakeholder collaboration, and established a foundation for sustainable community-based solid waste management in support of coastal environmental sustainability.